UPAYA MENINGKATKAN KEBUGARAN JASMANI SISWA KELAS II A MELALUI PENERAPAN MODEL CIRCUIT TRAINING DI SDN 1 LANDASAN ULIN SELATAN - Fahreza, Ilham; Akbar Fauzan, Lazuardy; Suadmaji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of physical fitness of class II A students in Physical Education, Sports, and Health (PJOK) at SDN 1 Landasan Ulin Selatan. This condition is evident from the results of initial observations which show that most students get tired easily and are less active in participating in learning activities. This study aims to improve students' physical fitness through the implementation of the circuit training model. The study used the Classroom Action Research (CAR) method which was carried out in two cycles, with the stages of planning, implementation, observation, and reflection. The research subjects were 22 class II A students of SDN 1 Landasan Ulin Selatan. Data collection techniques included observation, physical fitness tests, and documentation, while data analysis was carried out descriptively comparatively by comparing the results of the pre-cycle, Cycle I, and Cycle II. The results showed a gradual increase in students' physical fitness. Learning completeness in the pre-cycle stage was 31.82%, increased to 68.18% in Cycle I, and reached 86.36% in Cycle II. Thus, the application of the circuit training model has been proven to improve the physical fitness of class II A students at SDN 1 Landasan Ulin Selatan in PJOK learning.